Drawing is Learning - Laurence Musgrove; Myra Musgrove (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
JAEPL’s guru of visual pedagogy visits the origins of his strategy for teaching through “handmade thinking,” which gives students the freedom to re-conceptualize how they read and write.